Garlic Extract to Increase Platelet Levels in Dengue Hemorrhagic Fever Patients - Eni Kusyati; Ni Nyoman M A (Health Notions, 2017)
The case of DHF in Central Java is quite high. Nearly all blood lab results of patients with DHF are reported to show significant decreases in platelet count. Garlic extract is known to inhibit platelet aggregation induced by Adenosine diphosphate (ADP), epinephrine, collagen and arachidonate, and may inhibit prostacyclin biosynthesis. Diallyl disulphide (DADS) and diallyl trisulphide in garlic can prevent thrombus formation. The essential compounds contained in garlic are thought to increase the blood platelet count in DHF patients. The purpose of this study was to add non-pharmacological treatment reference to increase platelet count in DHF patients. This study used a true experimental design. The sample of this study were 22 DHF patients in "Nakula 2" and "Nakula 3" Disease Hospital Semarang City Hospital. The data were analyzed using T-test. The results showed that garlic extract could increase platelet count in DHF patients. Keywords: DHF, Garlic extract, Platelet